Un Grande Fotogrammetra Licinio Ferretti - Selvini, Attilio (GEOmedia, 2014)
The article shows the history of the "Commander" Licinio Ferretti and his relationship with cartography, topography photogrammetry and aeronautics. Since the birth of CGR to the first aerial co verage of Italy until partecipation with SIFET and the establishment of ASITA .